Fundamental bioengineering - Villadsen, John (Advanced biotechnology., 2016)
A thorough introduction to the basics of bioengineering, with a focus on applications in the emerging "white" biotechnology industry. As such, this latest volume in the "Advanced Biotechnology" series covers the principles for the design and analysis of industrial bioprocesses as well as the design of bioremediation systems, and several biomedical applications. No fewer than seven chapters introduce stoichiometry, kinetics, thermodynamics and the design of ideal and real bioreactors, illustrated by more than 50 practical examples. Further chapters deal with the tools that enable an understanding of the behavior of cell cultures and enzymatically catalyzed reactions, while others discuss the analysis of cultures at the level of the cell, as well as structural frameworks for the successful scale-up of bioreactions. In addition, a short survey of downstream processing options and the control of bioreactions is given.With contributions from leading experts in industry and academia, this is a comprehensive source of information peer-reviewed by experts in the field.